Clinical Outcomes of Fifth Metatarsal Fractures using Jones Fracture-Specific Screw vs Intramedullary Fixation. Issue 4 (November 2022) - Anastasio, Albert T.; Chopra, Aman; Fletcher, Amanda N.; Sharma, Akhil; Parekh, Selene G.
Category: Midfoot/Forefoot Introduction/Purpose: Fractures of the proximal fifth metatarsal (Jones fractures) are common foot injuries in both athlete and nonathlete populations, given repetitive loading of the lateral column during gait. Intramedullary screw fixation is the current most common surgical management for Jones fractures, but high rates of nonunion and refracture as well as hardware prominence are reported with existing implant options for this fracture pattern. The Jones bolt is a novel surgical treatment for Jones fractures which aims for more anatomic fixation of this injury. The purpose of this study was to compare the Jones bolt to intramedullary screw fixation with regard to complication rates and patient reported outcomes. Methods: A retrospective single-surgeon case series was approved by our institutional review board. A sample of both athletes as well as nonathletes with proximal fifth metatarsal fractures treated with either intramedullary screw fixation or the Jones bolt was collected. Demographic data, patient reported outcomes, and complication rates were analyzed. Results: Patients reported significant improvements in both visual analog scale (VAS) and the American Orthopaedic Foot & Ankle Society (AOFAS) scores following operative fixation of Jones fractures (Table 1). The average VAS score improved from 5.4+-2.6 preoperatively to 1.4+-1.7 postoperatively (p<0.0001). The average AOFAS score improved from 59.0+-13.2 preoperatively to 186.0+-11.2 postoperatively (p<0.0001). There was no difference in final postoperative VAS (1.4 vs. 1.4; p=0.9702) or AOFAS (87.7 vs 85.7; p=0.4262) or overall change of VAS (3.8 vs. 3.5; p=0.8219) or AOFAS (20.5 vs. 25.0; p=0.6613) for Jones bolt versus all other types of fixation. Conclusion: The Jones bolt is a novel treatment for proximal fifth metatarsal fractures, with noninferior outcome scores and complication rates when compared with intramedullary screw fixation. Long-term follow-up and larger sample sizes are indicated to assess for superiority of the Jones bolt.